Enhancing Students’ Higher-Order Thinking Skills through the Implementation of a Scientific Approach to Hydrocarbons - Subaeri Subaeri; Sri Rahayu; Siti Marfu’ah (J-PEK (Jurnal Pembelajaran Kimia), 2025)
This research focuses on improving students’ higher-order thinking skills (HOTS) in hydrocarbon chemistry by developing teaching materials grounded in a scientific approach. To assess the effectiveness of the learning described above, this research employs a mixed-methods approach, collecting observational data and administering questionnaires to high school students at SMAN 1 Paiton, Probolinggo Regency. In practice, this research produces teaching materials on hydrocarbons developed using a scientific approach and assessed by expert validators. The average suitability scores are 91.06% for teachers' books and 91.72% for student books, both rated as very feasible. Furthermore, the independent-samples t-test revealed a significant difference between the experimental and control classes (p = 0.012; <0.05). Qualitative findings also indicate that the use of these teaching materials is highly feasible and necessary to improve HOTS among students.